Agrimonia eupatoria L. (Agrimony) Extract Alters Liver Health in Subjects with Elevated Alanine Transaminase Levels: A Controlled, Randomized, and Double-Blind Trial - Cho, Young Mi; Kwon, Jeong Eun; Lee, Minkyung; Lea, Youngsung; Jeon, Do-Yong; Kim, Hyeong Jun; Kang, Se Chan (Journal of medicinal food, 2018)
Agrimonia eupatoria L. has been shown to protect against liver injury due to its lipid lowering and antioxidant activities. The aim of this research was to evaluate the effect of A. eupatoria L. aqueous extract (AEE) on 80 subjects with elevated alanine transaminase (ALT) levels in a randomized, double-blind, placebo-controlled, 8-week study. This trial was conducted between January 2013 and July 2013 at the Oriental Medical Hospital (Jecheon) of Semyung University. The trial included subjects aged 20 years or older who were diagnosed with mildly to moderately elevated ALT levels (between 45 and 135 IU/L). Subjects received two capsules of placebo or AEE twice a day for 8 weeks. Adverse events were recorded. Eighty subjects were randomized to placebo or AEE groups who had similar baseline characteristics. During the 8 weeks of treatment, 11 subjects were excluded from the analysis for protocol violation or consent withdrawal; efficacy of treatment was, therefore, evaluated in 69 subjects (placebo = 35, AEE = 34). The AEE group showed a significant reduction in ALT and serum triglyceride (TG) at 8 weeks compared with the placebo group (ALT P = .044, TG P = .020). Significant group and time interactions were found in ALT (P = .038), aspartate aminotransferase (P = .040), and TG (P = .010). Alkaline phosphatase, total bilirubin, and gamma-glutamyl transferase levels were not different between the two groups. There were no reported severe adverse events during this study, and total protein, albumin, blood urea nitrogen, creatine, and total cholesterol levels were normal in both groups. AEE consumption was safe and generally well tolerated without severe adverse events.